Kualitas Peningkatan Pelayanan Publik Menuju Aparatur Sipil Negara (ASN) Bertaraf Internasional - Adhy Yulianto; Harsoyo Harsoyo (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
The purpose of this research is to examine initiatives to enhance the quality of public services. in order to achieve service standards that are on par with international standards for the State Civil Apparatus (ASN). This study employs a qualitative method with a case study at a local government agency. that has been recognized as the agency with the best quality public services. In-depth interviews with government officials were used to acquire data., employees and customers, as well as analisis of documents related to the implemented public service improvement program. According to the study's findings, local government agencies have succeeded in improving the quality of public services by implementing a number of strategic initiatives and programs. Among them are the effective use of information technology to improve efficiency and effectiveness accessibility of public services, training and human resource development to improve employee skills and professionalism, and implementing strict service standards to measure and ensure customer satisfaction. In an effort to achieve international civil state standards (ASN), local government agencies have set several main goals, including improving communication and speaking foreign languages, mastery of advanced public information technology and application of ethics and integrity in public administration. serve. function. service assignment. In addition, international recognition ISO (International Organization for Standardization) and others awards for quality of public services are successful goals pursued by these bodies.